Hearing Performance in Cochlear Implant Users Who Have Facial Nerve Stimulation - Rocha, Larissa Veloso; Goffi-Gomez, Maria Valéria Schmidt; Hoshino, Ana Cristina; Tsuji, Robinson Koji; Bento, Ricardo Ferreira (International Archives of Otorhinolaryngology, 2023)
Introduction Facial nerve stimulation (FNS) is a complication in cochlear implant (CI) when the electrical current escapes from the cochlea to the nearby facial nerve. Different management to reduce its effects are available, although changes might result in a less-than-ideal fitting for the CI user, eventually reducing speech perception.Objective To verify the etiologies that cause FNS, to identify strategies in managing FNS, and to evaluate speech recognition in patients who present FNS.Methods Retrospective study approved by the Ethical Board of the Institution. From the files of a CI group, patients who were identified with FNS either during surgery or at any time postoperatively were selected. Data collection included: CI manufacturer, electrode array type, age at implantation, etiology of hearing loss, FNS identification date, number of electrodes that generated FNS, FNS management actions, and speech recognition in quiet and in noise.Results Data were collected from 7 children and 25 adults. Etiologies that cause FNS were cochlear malformation, head trauma, meningitis, and otosclerosis; the main actions included decrease in the stimulation levels followed by the deactivation of electrodes. Average speech recognition in quiet before FNS was 86% and 80% after in patients who were able to accomplish the test. However, there was great variability, ranging from 0% in quiet to 90% of speech recognition in noise.Conclusion Etiologies that cause FNS are related to cochlear morphology alterations. Facial nerve stimulation can be solved using speech processor programming parameters; however, it is not possible to predict outcomes, since results depend on other variables.
Keywords: hearing loss; cochlear implantation; rehabilitation; facial nerve